Lessons learned from the Advancing Maternal Immunization collaboration: identifying evidence gaps for informed respiratory syncytial virus maternal immunization decision-making [version 1; peer review: 2 approved] - Devin Groman (Gates Open Research, 2019)
In an increasingly crowded vaccine landscape, global and country decision-makers will require evidence-based and disease-specific information when prioritizing new public health interventions. The Advancing Maternal Immunization collaboration (AMI) was designed to develop a cross-program strategy to advance respiratory syncytial virus (RSV) maternal immunization (MI) availability and accessibility in low- and middle-income countries by completing a comprehensive RSV MI gap analysis and developing an actionable roadmap report. By engaging and coordinating key stakeholders using a web-based communication platform and developing standardized tools, AMI was able to facilitate interaction and consensus between members. This paper describes the methodology used to create and manage AMI’s work. We share lessons learned from our approach to inform other groups conducting similar work requiring cross-sectoral engagement. This approach could be adapted to efficiently conduct gap analyses for other health interventions that require input and coordination across a variety of topic areas, disciplines, geographies, and stakeholders.